Cost-efficient climate policies for interdependent carbon pools. (March 2018) - Elofsson, Katarina; Gren, Ing-Marie
Abstract: The purpose of this paper is to investigate cost-effective climate policy instruments for bioenergy and timber, adapted to the impacts on interdependent forest carbon pools, and applied in the EU climate policy to 2050. We develop a discrete time dynamic model including forest carbon pools in biomass, soil, and products, as well as fossil fuel consumption. The analytical results show that the optimal taxes on forest products depend on the growth in the respective carbon pool. The application to the EU 2050 climate policy for emission trading shows that total costs for target achievement can be reduced by 33 percent if all carbon pools are included, and the carbon tax on fossil fuel can be reduced by 50 percent. Optimal taxes on forest products differ among countries and over time depending on the potential for increased carbon sequestration over the planning period. Highlights: We model forest carbon sequestration in EU climate policy from 2010 to 2050. We examine the cost-efficiency of increases in 3 different forest carbon pools. Inclusion of all carbon pools reduces costs by 33% and carbon price by up to 50%. Separate inclusion of biomass or soil pools in the policy yields positive effects. Uniform EU-wide carbon taxes on timber and bioenergy are inefficient.